TINJAUAN DAN KONSEP INVESTAS1 SYAR1’AH - Dadang, Asep (Jurnal Ilmu Akuntansi dan Bisnis Syariah (AKSY), 2020)
This article discusses the objectives and concepts of shari’ah investment. Based on the release of the OJK Investment Alen Task Force, during 2019 there were 444 entities that were terminated for carrying out business activities that were allegedly carried out without permission from the competent authorit y and potentially detrimental to the communit y. Sharia investment is an investment based on sharia principles, both investment in the real sector and financial sector, investment cannot be separated from sharia principles. This research is qualitative withÂ aÂ literature study approach with data sources, namely secondary data from previous research and other reference data sources. lnrestmentÂ is an investment activity in the hope that you will get a profit in the future. Islam teaches people to strive for a better life in the world and the hereafter. Having a good life in this world andÂ inÂ the hereafter that can guaranteeÂ theÂ achievementÂ ofÂ physicalÂ and mental welfare (falah). The purposeÂ ofÂ investing,Â amongÂ others, is to obtain maximum profits, guarantee future, protectÂ profits, obtain passive income, realize the desire to achieve the afterlife goals. SomeoneÂ whoÂ willÂ makeÂ anÂ investmentÂ shouldÂ pay attention to the conditions that areÂ prohibitedÂ andÂ thatÂ are allowed in investing so that it benefits him for the world and the hereafter. With the concept that all propeny and all means of production are essentially God’s absolute, whereas humans are only limited to getting the mandate to manage it to be useful in life. Â Keywords : Objectives, Concepts, Sharia Investment, Speculation